2014
DOI: 10.1007/s00520-014-2377-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving hospital performance in the treatment of febrile neutropenia

Abstract: Improvements in the management of FN can be accomplished and sustained by the focused study of performance of individual tasks, the design of streamlined processes by practitioners, and the ongoing review of performance with feedback to clinical departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… 49 , 51 FN management can also be improved through the design and implementation of more efficient processes, to overcome barriers preventing the timely administration of antibiotics. 1 , 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“… 49 , 51 FN management can also be improved through the design and implementation of more efficient processes, to overcome barriers preventing the timely administration of antibiotics. 1 , 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Meisenberg et al showed the longest delayed treatment were a consequence of the conscious or functional decision to pause the delivery of antibiotics while awaiting transfer to an inpatient unit. This delayed treatment is a result of lack of appreciation for the pathophysiology of infection and potential sepsis (11).…”
Section: Discussionmentioning
confidence: 99%
“…1. Thirty studies were included, thirteen in adult [12,[20][21][22][23][24][25][26][27][28][29][30][31], and seventeen in pediatric patients [16,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], including a total of 1891 and 6820 FN episodes, respectively. Two-third of the studies were undertaken in the USA (n = 20; 67%).…”
Section: Overviewmentioning
confidence: 99%